2000
DOI: 10.1080/07391102.2000.10506639
|View full text |Cite
|
Sign up to set email alerts
|

Drug Self-Assembly on DNA: Sequence Effects withtrans-bis-(4-N-methylpyridiniumyl)diphenyl Porphyrin and Hoechst 33258

Abstract: Self assembly in biological systems is increasingly being recognised as an important phenomenon. We have examined two model systems: the cationic meso-substituted free base porphyrin derivative frans-bis-(4-N-methylpyridiniumyl)diphenyl porphyrin (t-H(2)P) and Hoechst 33258 (Hoechst) both of which were known to assemble on DNA. t-H(2)P self-assembles in solution under appropriate conditions, whereas Hoechst does not. By varying ionic strength and ligand: DNA mixing ratios, these features together with their di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…In other words, R ¼ 1 indicates 1 porphyrin per 12 basepairs and base triplets for the 12mer duplex and triplex, respectively, and 1 porphyrin per 6 basepairs for 6mers. The appearance of spectra for the porphyrin-DNA system is affected by the order of mixing (Ismail et al, 2000). Therefore, in this study, aliquots of concentrated TMPyP (typically ;200 mM) were always added last to the DNA solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, R ¼ 1 indicates 1 porphyrin per 12 basepairs and base triplets for the 12mer duplex and triplex, respectively, and 1 porphyrin per 6 basepairs for 6mers. The appearance of spectra for the porphyrin-DNA system is affected by the order of mixing (Ismail et al, 2000). Therefore, in this study, aliquots of concentrated TMPyP (typically ;200 mM) were always added last to the DNA solution.…”
Section: Methodsmentioning
confidence: 99%
“…It has been known that some porphyrins stack by themselves in aqueous solution (Ismail et al, 2000;Pasternack et al, 2001) and produce hypochromism in the Soret absorption region. The extent of the self-stacking depends on the salt and porphyrin concentration.…”
Section: Self-stacking Of Tmpyp In Aqueous Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays the ligands noncovalently binding with DNA are divided into two classes -intercalators and groove binding compounds [8][9][10][11][12][13][14][15][16]. However, the results of theoretical and experimental investigations show that depending on the external medium conditions several ligands may bind to double-stranded (ds-) or single-stranded (ss-) DNA in more than one mode (multimodal ligands) [17][18][19][20][21][22][23][24][25]. From this point of view methylene blue (MB, Fig.…”
mentioning
confidence: 99%
“…It was shown [7] that porphyrin plane molecules TMPyP intercalate between the base pairs of DNA double helix and they bind only to 5'CG3' areas, and not to other sequences. Outside binding modes were studied in works [6][7][8][9][10][11]. It was also shown that these binding modes were formed mainly by porphyrins having axial ligands, which were absorbed on AT rich areas located in minor and major grooves, as well as double helix surface of DNA [12].…”
Section: Introductionmentioning
confidence: 99%